2009
DOI: 10.1160/th08-07-0491
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin amino terminal region helps protect coagulation factor Va from proteolytic inactivation by activated protein C

Abstract: SummaryThe hypothesis that prothrombin (FII) protects coagulation factor Va (FVa) from proteolytic inactivation by activated protein C (APC) was tested using purified proteins. FII dose-dependently protected FVa from APC proteolysis under conditions where competition of proteins for binding to negatively-charged phospholipid surface was not relevant (i.e. either at high phospholipid vesicle concentrations or using soluble dicaproylphosphatidylserine at levels below its critical micellar concentration). Cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…Inhibition of prothrombinase by APC(S360A) is enhanced at low FXa concentrations. Prothrombin effectively abolished the anticoagulant effect APC(S360A) in the model system, which is in agreement with recent results (34). These observations are in line with an anticoagulant mechanism in which APC(S360A) inhibits the cofactor activity of FVa by competing with FXa and prothrombin for binding to FVa.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Inhibition of prothrombinase by APC(S360A) is enhanced at low FXa concentrations. Prothrombin effectively abolished the anticoagulant effect APC(S360A) in the model system, which is in agreement with recent results (34). These observations are in line with an anticoagulant mechanism in which APC(S360A) inhibits the cofactor activity of FVa by competing with FXa and prothrombin for binding to FVa.…”
Section: Discussionsupporting
confidence: 92%
“…The binding regions on FVa for prothrombin have been less well described. However, the fact that prothrombin inhibits APC-catalyzed FVa inactivation in the absence of FXa (33)(34) suggests that APC and prothrombin also share binding sites on FVa. The protective effect of prothrombin in the presence of OG-FXa can be explained by formation of a nonproductive ternary OG-FXa⅐FVa⅐prothrombin complex.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from protein S, several other factors modulate FVa inactivation in vivo . In particular, when FVa is incorporated in the prothrombinase complex, it is protected from APC‐mediated inactivation by interactions with FXa, which specifically protects the Arg 506 cleavage site [18,19], and with prothrombin, which inhibits cleavage at both Arg 306 and Arg 506 [20–22]. These protective effects are abrogated by protein S [19,21].…”
Section: The Protein C Anticoagulant Pathwaymentioning
confidence: 99%
“…Guinto and Esmon reported that prothrombin protects the intact FVa molecule by competing with APC for binding to FVa [58]; more recent studies have reported a K D of between 500–700 nM for FVa and prothrombin [39,40]. …”
Section: Resultsmentioning
confidence: 99%